Spectrophotometery hasn't been this simple since we invented it. - Beckman Instruments, Inc. (1984)
This advertisement for the new DU-50 Series Spectrophotometers uses Beckman Instruments' history as an innovator and dependable source of spectrophotometers to market their new product. This new line offers programmable test parameters, which can be created by the end user, stored on a memory card that comes with the instrument, and then used for future tests. The first Beckman Instruments DU Spectrophotometer was developed in 1940, when the company was still called National Technical Laboratories. Spurred by employee Howard Cary (who had previously been involved in pH meter development), NTL produced its first DU Spectrophotometer in 1940. This first Model A contained a glass prism, while subsequent models used quartz crystal. The DU was initially developed under a U.S. government contract, but was ultimately used in many important scientific discoveries and developments of the 20th century, including penicillin and synthetic rubber research, petroleum refining, and the creation of explosives.
Keywords: Scientific apparatus and instruments; Spectrophotometer; Spectrophotometry; Beckman Instruments, Inc.